2022
DOI: 10.1371/journal.pone.0274348
|View full text |Cite
|
Sign up to set email alerts
|

Three weeks of rehabilitation improves walking capacity but not daily physical activity in patients with multiple sclerosis with moderate to severe walking disability

Abstract: Background Patients with multiple sclerosis have low levels of physical activity. This is of concern because low activity levels are related to cardiovascular disease, poor walking ability, and reduced quality of life. The aim of this study was to evaluate the impact of rehabilitation on daily physical activity and walking capacity in patients with multiple sclerosis who have moderate to severe walking disability. Methods This exploratory, observational study of 24 patients with multiple sclerosis examined d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
2
1
0
Order By: Relevance
“…The improvements measured in TUG test of 15.4% and 12.0% in the mildly and severely disabled pwMS, respectively, are statistically significant but lower than the established threshold of 23% for genuine changes [ 40 ]. Our results confirm previous findings demonstrating statistically significant improvements in all clinical walking outcome measurements (i.e., 10mWT, 2MWT and TUG) after a physical rehabilitation program [ 13 , 14 , 22 , 26 ]. Taken together, these results demonstrate that pwMS with mild and severe disabilities benefit from the MIR by significantly and clinically improving their perceived and actual functional mobility.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The improvements measured in TUG test of 15.4% and 12.0% in the mildly and severely disabled pwMS, respectively, are statistically significant but lower than the established threshold of 23% for genuine changes [ 40 ]. Our results confirm previous findings demonstrating statistically significant improvements in all clinical walking outcome measurements (i.e., 10mWT, 2MWT and TUG) after a physical rehabilitation program [ 13 , 14 , 22 , 26 ]. Taken together, these results demonstrate that pwMS with mild and severe disabilities benefit from the MIR by significantly and clinically improving their perceived and actual functional mobility.…”
Section: Discussionsupporting
confidence: 91%
“…In the present MS cohort, mildly and severely disabled pwMS reported significant improvements in their walking ability as assessed by the MSWS-12 questionnaire (-6.6 and -9.4 points, respectively), which is in the range of clinically meaningful changes between -6 and -11 points [ 5 , 6 ]. The improvement in fatigue (FSMC) by -4 and -3 for mildly and severely disabled pwMS, respectively, is consistent with previous studies [ 26 , 33 ], but below the reported minimum for a clinical meaningful change (-9 points) [ 53 ]. In addition, pwMS also reported significant improvements in their self-rated health (EQ-VAS) of about + 10 and + 9 points for mildly and severely disabled pwMS (see appendix 3 in supplementary material).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation